PENGGUNAAN MEDIA PERMAINAN KARTU KUARTET PADA PEMBELAJARAN MENULIS KARANGAN NARASI - Amin Syahputra (Universitas Negeri Medan, 2012)
To be able to write, especially to write a narrative essay, students must first have an idea, the idea of ​​a skeleton events (conflict) at the same time and place the background. After that, then he can develop his idea into a narrative essay narrative intact. To that end, students need something that can be used as a source of inspiration or a source of ideas rather narrative. Temporal, cards quartet is four (quartet), each card contains a picture that explains the subtitle, while each card is linked to a subtitle headline. For example, the